PENGARUH TERAPI SENAM KAKI TERHADAP PENURUNAN GLUKOSA DARAH PADA LANSIA DENGAN DIABETES MELLITUS DI POSYANDU LANSIA DESA LEDUG KECAMATAN KEMBARAN BANYUMAS - Tri Sumarni; Danang Tri Yudhono (Universitas Harapan Bangsa Purwokerto, 2013)
The most health problems encountered in the elderly is a chronic disease that sometimesarise acutely and will suffer until death. Diabetes mellitus is a chronic disease that is oftenfound in elderly populations. Physical exercise is one of the four pillars of the implementation ofdiabetes mellitus because it can decrease glucose levels in the blood. One exercise thatrecommended in the elderly population is gymnastics feet. To know influence of gymnastics feet to degradation of blood glucose rate in elderly withdiabetes mellitus. This research conducted at health center of old age in Village Ledug DistrictKembaran. The type of this research is a quantitative with pre-experiment one group pretest andposttest design. Sampling using a total sampling technique with check-list form SOP and withthe glucometer brands Bionime GM 100 to measure 24 respondents. Analysis of the data usedthe Wilcoxon Signed Ranks Test. From these results there is a significant relationship between leg exercise therapy todecrease blood glucose in older adults with diabetes, where there the P value 0.014 <0.05.Most of the respondents experienced a decrease in blood glucose after doing gymnastics feettherapy. Based on the results of research are among the effect of gymnastic feet therapy todecrease blood glucose in older adult with diabetes mellitus, need for regular activitiesin exercise implementation in patients with diabetes mellitus. Keywords: Gymnastics Feet Therapy, Elderly and Diabetes Mellitus.